PENINGKATAN KUALITAS PEMBELAJARAN MELALUI MANAJEMEN KURIKULUM - Mustajib; Ni’matul Mahmudah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study aims to find out curriculum management strategies to improve the quality of learning at SMAN 1 Pare. The approach used in this study is descriptive and qualitative. Data collection methods include documentation, observations related to improving learning in the classroom, and interviews are conducted with curriculum waka about curriculum management strategies, and principals about their role as leaders in managing the educational process in schools. The sequential data collection process, data presentation, data verification, and conclusion drawing are part of the data analysis techniques used. The researcher uses triangulation techniques, namely triangulation of time, method, and source to ensure the accuracy of the data. Based on the results and discussions so far, the strategies carried out in the curriculum management process at SMAN 1 Pare are in the form of planning, implementation and evaluation processes in it. It has a great influence on the improvement and improvement of the quality of learning, then these efforts show a significant influence seen from the improvement of student learning outcomes at SMAN 1 Pare